Keberkesanan program keselamatan berasaskan tingkahlaku terhadap pencapaian keselamatan di industri minyak dan gas di Malaysia - M Halimatus Sakdiah,; R Krishna Gopal, (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2010)
Behavioural-based safety (BBS) programme is an accident prevention programme emphasized on the aspect of unsafe behaviour, which considerably new in Malaysia. The oil and gas industry is among the industries in Malaysia that has successfully implemented and sustaining the programme. The aim of this study is to measure and evaluate the effectiveness of BBS towards the safety performance in the oil and gas industry in Malaysia that certainly has owned an outstanding safety performance. Methodology : A cross-sectional study using secondary data involving five indicators in the safety performance in the department of health, safety and environment (HSE) was performed at one of the oil and gas refinery companies in Malaysia. These indicators were chosen based on the frequency of its occurrence from January 2004 to December 2008. Result : The results of the study show the presence of a significant difference in the incidence rates of near misses (p=0.008) and medical treatment cases (p=0.035) before and after the implementation of BBS and a very strong negative relationship (r=-0.885) between the incidence rates of near-misses and the rates of BBS observations done. However, analysis on unsafe behaviour does not show a significant reduction from 2006 to 2008. Instead, a significant reduction was seen on equipments failure from year 2006 to 2007 (p=0.021) and 2006 to 2008 (p=0.032). Conclusion : The study has proven that the BBS is effective towards the reduction of the indicators in the safety performance, involving only the incidence rates of the near-misses and the medical treatment cases. However, a very strong negative relationship only involves the incidence rate of near misses. A significant reduction was also seen on the occurrence of instrument failure, which is one of the root causes of near-misses. Although there is no significant reduction on thye unsafe behaviour, the reduction of equipment failure is expected to be related to the increase in the level of awareness and safe behaviour as a result of BBS implementation.